Hydrazine based facile synthesis and ordered assembly of metal nanoparticles (Au, Ag) on a bacterial surface layer protein template - Puranik, Sarang S.; Joshi, Hrushikesh M.; Ogale, S. B.; Paknikar, K. M. (Journal of Nanoscience and Nanotechnology, 2008)
An efficient and facile procedure is developed for concurrent in situ synthesis and ordered assembly of metal nanoparticles on a periodic two dimensional protein array. The S-layer protein of Bacillus subtilis exhibiting uniform pore size is used as template. Synthesis of gold and silver nanoparticles anchoring on the pores of S-layer is achieved by chemical reduction of respective metal salt laden protein template. Transmission electron microscopy reveals formation of well ordered and separated gold and silver nanoparticles with an average diameter of 6 +/- 1 nm and 4 +/- 1 nm, respectively. The periodic arrangement of nanoparticles is dictated by the native structure of S-layer protein array as the nanoparticle locations are found to be correlated to the nanosized pores of the crystalline S-layer array.
Keywords: Bacteria; Metal Nanoparticles; synthesis

N-doped TiO2 nanoparticle based visible light photocatalyst by modified peroxide sol-gel method - Jagadale, Tushar C.; Takale, Shrikant P.; Sonawane, Ravindra S.; Joshi, Hrushikesh M.; Patil, Shankar I.; Kale, Bharat B.; Ogale, Satishchandra B. (Journal of Physical Chemistry C, 2008)
The peroxide gel route is employed to synthesize N-doped TiO2 nanoparticles (NP) at low temperature using titanium tetraisopropoxide, ethylmethylamine, and hydrogen peroxide as precursors. Structural studies show anatase phase in the undoped titania NPs as well as at 5 at. % N-doped titania NPs, although with a degree of matrix disorder in the latter case. The annealing of N-doped titania NPs at different temperatures shows that above 400 degrees C nitrogen escapes the O-Ti-O matrix and at 500 degrees C the sample becomes crystalline. Transmission electron microscopy reveals that the particle size is in the range of 20-30 nm for the undoped TiO2 but only 5-10 nm for N-doped TiO2. At higher nitrogen concentration (10 at. %) bubble-like agglomerates form. FTIR and photoluminescence quenching also confirm the incorporation of nitrogen in anatase TiO2. Optical properties reveal an extended tailing of the absorption edge toward the visible region upon nitrogen doping. X-ray photoelectron spectroscopy is used to examine the electronic state of doped nitrogen and the associated possible electronic modification of the TiO2 matrix. Under visible light irradiation the undoped TiO2 NPs do not show any significant photocatalytic activity, as expected; however, the 5 at. % N-doped TiO2 NPs show excellent activity.